2018
DOI: 10.1158/1055-9965.epi-17-0547
|View full text |Cite
|
Sign up to set email alerts
|

Height, Obesity, and the Risk of TMPRSS2:ERG-Defined Prostate Cancer

Abstract: The largest molecular subtype of primary prostate cancer is defined by the gene fusion. Few studies, however, have investigated etiologic differences by status. Because the fusion is hormone-regulated and a man's hormonal milieu varies by height and obesity status, we hypothesized that both may be differentially associated with risk of -defined disease. Our study included 49,372 men from the prospective Health Professionals Follow-up Study. Participants reported height and weight at baseline in 1986 and update… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Men assayed for a molecular marker were more likely to be diagnosed in earlier years, to be younger at diagnosis, and to have more information regarding their clinical characteristics. Previous studies from our group suggest that statistically accounting for differences between cases with and without molecular marker information does not materially change results …”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Men assayed for a molecular marker were more likely to be diagnosed in earlier years, to be younger at diagnosis, and to have more information regarding their clinical characteristics. Previous studies from our group suggest that statistically accounting for differences between cases with and without molecular marker information does not materially change results …”
Section: Resultsmentioning
confidence: 75%
“…Lifestyle may also play a role in the development of PCa defined by TMPRSS2:ERG . For example, lycopene consumption from tomato products has been shown to be inversely associated with ERG‐positive but not ERG‐negative disease, and two studies have shown obesity to be associated with a reduced risk of developing TMPRSS2:ERG ‐positive PCa . Given that families often share lifestyle exposures, the association between a family history of PCa and molecular subtypes of PCa could operate through environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations